Keplerian ellipses : a student guide to the physics of the gravitational two-body problem - Reed, Bruce Cameron (IOP (Series). Release 22., 2023)
Kepler's three laws of planetary motion were a stunning development in human intellectual history. This second edition is a concise, self-contained treatment of Kepler/Newton planetary orbits at the level of an advanced undergraduate physics student. New to this edition are elements such as a detailed derivation of Newton's shell-point equivalency theorem, a revised derivation of the polar equation for an ellipse, Kepler's third law for non-inverse-square central potentials, a chapter on transfer and rendezvous orbits, and an expanded treatment of methods of calculating the average distance between the Sun and a planet. The approach is student-friendly, featuring brief sections, clear notation and diagrams, and mathematics that undergraduates will be comfortable with, accompanied by numerous exercises.